Pengembangan Website Dilan di Desa Sobayan Klaten - Pamungkas, Canggih Ajika; Puspitasari, Norma; Junior, Ryan (Jurnal Informa : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The information on most village websites in Sobayan Village, Klaten, is rarely updated. This community service aims to equip village devices with the skills to present data digitally and enhance the disseminated information. The activity is carried out in three stages: preparation, training, evaluation, and instruction. Participants are assisted for one month, and their information will be updated on the village website. 90% of the village devices that undergo training update information on the website. The development methods used include stakeholder needs identification, sustainability analysis, user-friendly interface design, and implementation of appropriate technology. Continuous evaluation is conducted during the development process to ensure the effectiveness and sustainability of the website.Research results indicate that website development in villages can be an effective tool to expand information access, enhance community participation, and strengthen social connectivity at the local level. This activity provides valuable insights into how information technology can be strategically used to improve social and economic conditions in villages. Practical implications of these findings can guide website development efforts in other villages, reinforcing the role of technology in supporting sustainable development at the local level. This activity involves active collaboration between web developers, village governments, and local community members to ensure that the website can provide maximum benefits.